Adversity Quotient as a Predictor of Creative Thinking Skills in Solving Algebraic Problems among Junior High School Students - Hariyani, Sri; Mustafa, Sriyanti; Musa, Muzirah (FKIP Universitas Lampung, 2025)
This study emphasizes the importance of creative thinking skills as a key 21st-century student competency. Observations at a junior high school in Malang City revealed that 68% of 31 students could not solve simple algebra problems. This inability could be caused by several factors, one of which is low creative thinking skills. There is still limited research on creative thinking skills. Therefore, this study aimed to assess pupils’ original ideas and abilities in algebra questions based on AQ (Adversity Quotient) categories. In this qualitative descriptive research, 33 students were selected based on various AQ categories. The AQ data were collected through a questionnaire and categorized as follows: 11 students in the Climbers category, 17 in the Campers category, and five in the Quitters category. Three subjects were selected based on the highest scores in each category: AQ, representative, and communicative. The subjects were further analyzed using a creativity component test (fluency, flexibility, and originality). The data collection methods in this investigation were the AQ questionnaire, a creative thinking ability test, and semi-structured interviews. The interviews aimed to gather more in-depth information about students’ thought processes while solving algebra problems. The study’s results indicate that the majority of students are in the Campers category (51.51%), followed by Climbers (33.33%) and Quitters (15.15%). Students with AQ Climbers profiles meet the fluency, flexibility, and originality criteria. Students with AQ Campers appear confident, but their solutions did not meet the fluency component (fulfilling the components of flexibility and originality). Meanwhile, pupils who are AQ Quitters cannot meet the requirements for creative thinking. The conclusion of this study is that the higher the level of resilience (AQ) of students, the higher their ability to think creatively and solve mathematical problems fluently, flexibly, and originally. This research can inspire teachers to use the open-ended problem-solving method by considering students’ AQ levels, helping students enhance their creative thinking skills. Keywords: adversity quotient, creative thinking skills, algebra.